Implications of the principle of involvement in learning design at elementary school level - Debora Pratiwi Sibarani; Rachmy Aryati Nurdin (xxxx-xxxx, 2023)
A learning process requires the direct involvement of students to develop their potential to prepare them to seek opportunities and manage the challenges of the coming smart society 5.0. However, the involvement of students does not guarantee active learning in the classroom. This article will define the principle of involvement in learning, describe two learning approaches that can engage students in learning physically, mentally, emotionally, and intellectually, and explain the implications of these learning approaches in concrete learning for educators and students. This article used a literature review as a qualitative method to describe the principle of involvement through two learning approaches, namely John Dewey's Learning by Doing Theory and Barrows and Tamblyn's Problem-Based Learning (PBL) Method. Hence, the readers can see how important the principle of involvement in learning is and its implications as the teacher's ability to serve not only as a facilitator, but also as an activity manager who is able to direct, guide, and encourage students toward predetermined learning goals. Therefore, the direct involvement of students in the learning process is absolute because those experiences aim to alter and enrich them in acquiring the 21st-century skills needed.